Comparison of Polycyclic Aromatic Hydrocarbons Exposure Across Occupations Using Urinary Metabolite 1-Hydroxypyrene. Issue 4 (17th February 2020) - Koh, Dong-Hee; Park, Ju-Hyun; Lee, Sang-Gil; Kim, Hwan-Cheol; Choi, Sangjun; Jung, Hyejung; Park, Donguk
Abstract: Objectives: Polycyclic aromatic hydrocarbons (PAHs) are well-known carcinogens causing lung and skin cancers in exposed workers. Certain occupations, such as coke production, have been associated with high PAH exposure; however, the number of occupations tested to date remains small. Here, we sought to compare PAH exposure across a wide range of occupations based on levels of 1-hydroxypyrene (1-OHP), the urinary exposure surrogate of PAHs. Methods: We collected urine 1-OHP data from the Korean National Environmental Health Survey (KoNEHS), a nationwide biomonitoring survey. We developed a linear regression model, controlling for sex, age, smoking, and survey cycle, and obtained resulting residuals. Then, we computed the fraction of exceeding the third quartile (Q3) level of residuals for each occupation, which is employed as a relative exposure indicator across occupations. Results: A total of 15 125 measurements derived from three cycles of KoNEHS were used for analysis. The overall geometric means (GMs) and geometric standard deviation (GSD) of urine 1-OHP levels were 0.16 µg g −1 creatinine and 3.07, respectively. Among the sub-major occupational groups, 'construction and mining related elementary occupations' showed the highest fraction (0.45) of exceeding the Q3 level of residuals. Among the minor occupational groups, 'deliverers' showed a high fraction (0.42) of exceeding the Q3 level of residuals, which indicates rapidly growing occupations to be addressed. Conclusions: Our results provide ancillary information regarding PAH exposure across occupations, especially for occupations for which PAH exposure has not been well characterized.